Pendidikan Karakter dalam Kurikulum 2025: Masihkah Relevan di Era AI? - Suharmi, Suharmi; Haeruddin, Haeruddin; Akhmad, Akhmad (Universitas Pahlawan Tuanku Tambusai, 2025)
Technological advances, particularly artificial intelligence (AI), have driven major transformations in the education system, including in Indonesia. The 2025 Curriculum is a response to this dynamic, positioning the Pancasila Student Profile as the central axis balancing 21st-century competencies with character building. However, the digital era also brings serious challenges such as disinformation, value deculturation, and social alienation, which threaten the moral integrity of the younger generation. This article aims to systematically analyze the strategic role of character education in the 2025 Curriculum and formulate an integrative strategy between character and technology. Using a qualitative approach based on literature, this research examines curriculum policies, character education practices, and the potential use of AI to support value-based learning. The analysis shows that character education cannot be replaced by technology, as character is formed through affective, reflective, and social processes that can only be facilitated by human interaction. However, AI can be an effective tool if designed ethically and contextually, such as through project-based learning, digital storytelling, gamification, and character e-portfolios. Therefore, the integration of character education and technology in the 2025 Curriculum presents a strategic opportunity to shape students who are not only intellectually intelligent but also morally resilient in the digital age.